CHATGPT AS A TOOL FOR EFL LEARNING: ITS IMPACT ON MOTIVATION AND ENGAGEMENT - Ragiel Nandasyah; Sunarti Sunarti; Abdul Halim (Getsempena English Education Journal, 2025)
This study focuses on the impact of ChatGPT, an artificial intelligence-based language model, on students’ motivation and engagement in learning English as a Foreign Language (EFL). The research employs both qualitative and quantitative research methodologies, combining data collected through questionnaires and semi-structured interviewing. The sample included 133 EFL students from Universitas Muhammadiyah Kalimantan Timur, with additional narratives gathered from three selected participants. Quantitative findings reflected high levels of motivation (M = 23.89) and engagement (M = 22.88), with a strong positive correlation (r = .767, p < .01) between the two variables. Motivation was significantly higher than engagement based on the Mann-Whitney test. The qualitative findings reveal the uses of ChatGPT by the students as grammar correction, translation, and writing, which improved their confidence and learning interest. In contrast, some of the students expressed dependence on the tool and encountered issues of incorrect generation and lack of access in the free version. Despite all this, the participants expressed the need of using ChatGPT as a support tool rather than a replacement for independent learning. This study aims to address gaps in prior studies that examined ChatGPT’s benefits but rarely compared students’ motivational and engagement levels using both quantitative and qualitative lenses, this research offers a more comprehensive analysis of how learners experience AI-assisted language learning. The study concludes that ChatGPT can be an effective tool when used strategically. It offers practical implications for integrating AI in language education and encourages the development of digital literacy and critical thinking among learners.